Empowering Accounting Educators: Innovative Development through Community Engagement - Sigit Hermawan; Imelda Dian Rahmawati; Sriyono; Amelia Nugraha Dini; Anis Masrifah (Indonesian Journal of Cultural and Community Development, 2023)
This study underscores the imperative for continuous teacher development by elucidating an innovative community engagement endeavor aimed at augmenting the proficiency of accounting educators within the Sidoarjo Regency's Subject Teachers Forum (Musyawarah Guru Mata Pelajaran – MGMP). Employing a triad of methodologies encompassing awareness campaigns, training modules, and mentorship, the initiative proffers a curriculum centered on teaching factory concepts, financial technology integration, and millennial business trends. Evidenced by amplified pre- to post-test scores, the outcomes reveal a discernible upswing in pedagogical acumen following program participation. Qualitatively, heightened post-training dialogues showcase expanded knowledge domains concerning the aforementioned subjects, bolstering the claim of qualitative competence enhancement. This pioneering approach holds potential implications for fostering transformative teaching paradigms in the global pedagogical landscape. Highlights: Innovative Engagement: This study presents an inventive community engagement strategy that redefines teacher development through collaborative initiatives. Targeted Curriculum: The program introduces a curriculum emphasizing teaching factory concepts, financial technology integration, and millennial business trends, fostering contemporary pedagogical approaches. Measured Impact: Quantitative improvement observed in pre- and post-test scores is substantiated by qualitative enhancements, underscoring the efficacy of the engagement in elevating accounting educators' proficiency. Keywords: Accounting educators, Competence enhancement, Community engagement, Pedagogical innovation, Teacher development.